Integrasi Nilai-Nilai Toleransi dalam Media Sosial sebagai Sarana Edukasi Multikultural - Elisa Prima Sari; Rahma Talita Syahada; Taat Wulandari (Jurnal Ilmu Sosial dan Humaniora, 2026)
The development of digital technology has brought significant changes in the patterns of social interaction, particularly through the use of social media as a means of communication, information exchange, and public opinion formation. The presence of social media allows people to interact without limitations of space and time, thus accelerating the spread of information, culture, and social values ​​in a multicultural society. In the context of Indonesia, which has cultural, religious, and ethnic diversity, the value of tolerance is an important aspect in maintaining social harmony and strengthening unity. However, social media not only has a positive impact, but is also often used as a space for the emergence of intolerance, hate speech, discrimination, hoaxes, and social conflict due to the low digital literacy of the community. This study aims to examine the integration of tolerance values ​​in social media as a means of multicultural education in the digital era. The method used is a qualitative approach with a literature review. Data were obtained from various scientific sources, such as journals, books, articles, and previous research results relevant to the research topic. The results of the study indicate that social media has great potential as a medium for multicultural education through the distribution of educational content, digital campaigns, interactive discussions, and cross-cultural interactions that can increase understanding and appreciation of diversity. Furthermore, strengthening digital literacy, multicultural education, and collaboration between communities, educational institutions, governments, and social media platforms are crucial steps in creating an inclusive, safe, and tolerant digital space. With wise use, social media can be an effective tool for instilling values ​​of tolerance, empathy, and mutual respect in a multicultural society.